Analisa Penerapan Metode MOOSRA dan MOORA dalam Keputusan Pemilihan Lokasi Usaha - Sudarsono, Bernadus Gunawan; Zulkarnain, Iskandar; Buulolo, Efori; Utomo, Dito Putro (Building of Informatics, Technology and Science (BITS), 2022)
In the world of work, competition certainly exists. Especially in the selection of the location of the business being run. The better the location of the place of business, of course, the more competition. In this study, we will discuss the selection of a strategic and appropriate business location. The location of the business greatly affects the development of the business being run, many businesses do not develop (loss) so they have to stop their business because the location of the business is far from residential areas, the location is narrow and so on. To avoid this, we need a system that can solve the problem which is called a decision support system. Decision support system is a structured system in making effective business location selection decisions using methods such as WASPAS, SPI, TOPSIS, WP, SAW, MOORA, MOOSRA, EDAS and many others. The selection of business locations used the MOOSRA and MOORA methods. Both methods are very simple and easy to understand with the assessment based on the criteria used, namely Number of Competitors, Crowd Center, Location Size, Place Rent Price and Location Cleanliness. The results obtained after applying the two methods in the selection of business locations, namely the highest alternative or the first rank is Alternative A1 with a reference value of 0.564